A Coach's Dozen: An Update on Building Healthy, Strong, and Resilient Young Athletes. Issue 2 (April 2017) - Faigenbaum, Avery D.; Meadors, Larry
Abstract : ABSTRACT: THE "COACH'S DOZEN" IS A COLLECTION OF 12 PRINCIPLES THAT WILL HELP YOUTH COACHES, PHYSICAL EDUCATION TEACHERS, AND PEDIATRIC EXERCISE SPECIALISTS MAINTAIN INCLUSIVE, SUSTAINABLE, AND ENJOYABLE PARTICIPATION IN EXERCISE AND SPORT.